Pengaruh Employee Engagement dan Work Life Balance terhadap Turn Over Intention di Generasi Millenial - Lita Chrisdiana; Mukti Rahardjo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
The purpose of this study was to analyze influence of employee engagement (X1) and work life balance (X2) on turn over intention (Y) in millenial generation DKI Jakarta. This research used non-experimental quantitative design, with nonprobability and snowball sampling technique. Subject of this study consisted of thirty-one respondent who were work in Jakarta area, age between 20 until 36 years old. Data analysis is using multiple linear analysis with additional supported application of SPSS ver.23. result obtained from the data analysis showed with significance level 0,05, employee engagement (t-count = -1,162), which means Ho is accepted, which indicates there is a negative relationship between employee engagement and turn over intention. Moreover, work life balance (t-count = +2,534), which means Ho is rejected, which indicates there is a relationship between variable work life balance and turn over intention.